Caracterização edafoambiental da cafeicultura da região de Três Pontas, Minas Gerais - Bertoldo, Mathilde Aparecida (2014)
Due to the great importance of coffee in the south of Minas Gerais the purpose of this study was to map, characterize and evaluate the land occupied by coffee crops in the region of Três Pontas - MG, using geotecnonology. Therefore, information gotten for the images of the satellite Landsat 5, planialtimétrica chart of Três Pontas and secondary data was used, as maps of soil, agricultural aptitude of lands and geology. To develop the data base, the information was processed and analyzed in SIG SPRING. It was held a temporal analysis of the dynamics of use and occupation of land in the years of 1994, 2000 and 2007, characterization the dynamics of the coffee between the years of 1994 and 2007, and the edafoambiental evaluation, with generation of maps of classes of declivity, altitude, ground and agricultural soil suitability, in the intention of if getting greater precision and rapidity with application of this technology. The distribution of the use and occupation of lands in the area in study presents differences in the analysis space-temporal, demonstrating the dynamics of the activities for the three analyzed years and evidencing increase of culture areas. The use of GIS for characterization of the landscape for surveys and classification of soil from the 1:250.000 scale, has proved effective in the classes of slope was the variable that most influenced the model evaluated. The evaluation of the agricultural soil suitability demonstrated that the majority of the areas met in class 2(ab)c, with predominance of Latossolos, followed by the class 2ab(c) +3(a), with predominance of Argissolos and Nitossolos. The evaluation of the suitability of the crop coffee presented distribution according to the suitability of agricultural land and was little influenced by environmental requirements of culture.